COMBINING ABILITY STUDIES FOR GRAIN YIELD AND ITS COMPONENTS IN RICE (Oryza sativa L.) UNDER COASTAL SALINE SOIL CONDITIONS - CH. SURENDER RAJU, M. SUDHA RANI , P. RAGHAVA REDDY, V. RAVINDRA BABU, K. HARIPRASAD REDDY an (The Journal of Research, PJTSAU, 2017)
Combining ability studies on yield contributing characters through diallel analysis with eight genotypes ( RPBio-226, Swarna, CSR-27, CSR-30, CSRC(S)7-1-4, SR26-B, CST-7-1 and CSRC(S)5-2-2-5) was carried out during kharif, 2010 under salt affected soils of Agricultural Research Station, Machilipatnam. The study revealed the presence of higher specific combining ability (sca) variance for all the characters studied, suggesting the significant role of non-additive gene action. Based on gca effects, the genotypes CSRC(S)5-2-2-5, SR26B and CSRC(S)7-1-4 were identified as good combiners for yield attributing traits viz., number of tillers per plant, number of productive tillers per plant, panicle length, number of filled grains per panicle, 1000-grain weight, including yield. Hence, these parents could be exploited for development of salt tolerant high yielding varieties. Among the hybrids, Swarna x CSRC(S)7-1-4 was considered to be the best cross combination for seven traits viz., days to 50 per cent flowering, panicle length, panicle weight, number of filled grains per panicle, spikelet fertility, 1000-grain weight and grain yield per plant as per the sca effects and per se performance. The other hybrids with good specific combining ability for majority of the traits were SR26-B x CST-7-1, RPBio-226 x CSRC(S)7-1-4 and RPBio-226 x CSR-30 under saline soil conditions.